"They treat us like we're not there": Queer bodies and the social production of healthcare spaces. (May 2017) - Meer, Talia; Müller, Alex
Abstract: There is significant literature demonstrating the interpenetrability of identity and space, yet there is almost no work that explores the co-production of queer identities and healthcare spaces. We use Lefebvre's triad of (social) space to explore how the social spaces of South African healthcare facilities shape and are shaped by queer service-users, drawing on data from interviews and focus group discussions with 29 queer service-users and 14 representatives of organisations. Findings reveal that healthcare spaces are produced by the spatial ordering of health policy inattentive to queer health needs; the enduring symbolic representations of queerness as pathological or 'un-African'; and various identity assertions and practices of individuals, including queer service-users and healthcare providers. As a result, healthcare spaces are overwhelmingly heteronormative, although queer service-users' subversive practices suggest alternative spatial configurations. However, such resistance relies on individual empowered action and risks disciplining responses. Wider efforts are needed to transform the material and ideological space of healthcare facilities through law and policy reform and continuing professional training for healthcare providers.